Penerapan Mengoncek Kelapa di Desa Silo Lama Guna Mengetahui Cara Pembuatan dan Pemanfaatannya - Mahfudza, Amalia; Qolbi, Ahsana Zaida; Suryani, Lanny; Amarisa, Yassinta; Selian, Suci Nadilah; Lubis, Hilda Zahra (Ikatan Da'i Indonesia, 2023)
Coir stripping or known as stripping is also done using a tool made of iron in the form of a crowbar about 80 cm high with the sharp part facing upwards. At the bottom of this tool is given a seat so that the iron does not sink into the ground. Trained workers are able to peel an average of 500-1000 coconuts every day. This study uses a descriptive method that describes the facts that occur in the field. In this review, the researcher addresses the most common ways of gathering information through observation, interviews and documentation. Informants, in this case the residents of the old silo village, are direct sources of this data. This kind of data collection was used, among other things, to collect information from key informants, namely people who immediately knew about the problems being researched. In the old silo village of Teluk Nibung area in Tanjung Balai and Aer Joman in Asahan, the deputy governor visited points. Even though it is part of women’s empowerment, for Nurhajizah, wages of IDR 250-IDR 300 per kilogram are too low to be considered decent. Moreover, working from morning to evening, starting at 9.00-17.00, they receive only around Rp. 15-25 thousand per day. Application of Checking Coconuts In the old silo village to find out how to make and use it, the people in the village have one of their livelihoods, namely picking coconuts even though the wages are which can be obtained at a low nominal. Particularly for the female community, when they clean coconuts using their own knife, the way they peel them is very good and professional, so that the researchers who tried to peel the coconuts found it difficult and it was not as easy as it looked.